Variasi Bahasa dalam Debat Capres 2024: Penelitian - I. Sahur, Syamsurizal; N. Djou, Dakia; Kadir, Herson (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Language variation is very important because it can reflect how the character, personality, and ability of Presidential candidates to communicate with various levels of society. The purpose of this research is to find a variety of language variations in 2024 presidential debates. The problems raised in this study are (1) how language variation in the 2024 presidential candidate debate; and (2) what factors influence language variation in 2024 presidential candidate debate. This research uses a descriptive method with a qualitative approach. The data collection techniques used include listening and recording techniques. The data were analyzed based on the theory of Abdul Chaer and Leoni Agustina (2014). The data in this study are language variations and the data source in this study is the presidential debate video. The results of the study, namely, (1) the - use of language variation in 2024 presidential candidate debate, 88 data of language variation were found in 2024 presidential candidate debate, the variety of language variations found consisted of idiolect, dialect, chronolect, and sociolect, all the variations used by the presidential candidates were unique and different from one another. (2) Factors affecting language variation in 2024 presidential debate, several factors affecting language variation were found which were clearly described, namely factors, education, culture, work background, and situation and atmosphere that can affect the interaction process in a conversation.